Mouthpart Morphology of Three Sympatric Native and Nonnative Gammaridean Species: Gammarus pulex, G. fossarum, and Echinogammarus berilloni (Crustacea: Amphipoda). (22nd January 2012) - Mayer, Gerd; Maas, Andreas; Waloszek, Dieter
Abstract : In the last 20 years several nonnative amphipod species have immigrated inland waters of Germany and adjacent central European countries. Some of them have been very successful and could establish stabile populations. In some places, they have even replaced native or earlier established species. The gammarid Echinogammarus berilloni originates from the Atlantic region of France and the north-western part of Spain and coexists in some central European waters with the native Gammarus pulex and G. fossarum . Here, we describe and compare the mouthparts and other structures involved in food acquisition of these three sympatric gammaridean species. Our hypothesis was that differences in the mode of feeding of the three species could be the reason for their coexistence and that these differences would be expressed in differences in mouthpart morphology. The results of our SEM study demonstrate that there are indeed interspecific differences in details of the morphology of the feeding structures. This is especially true for the setation of antennae, maxillulae, gnathopods, and third uropods, which can be interpreted as adaptations to special modes of feeding. Generally, all three species are omnivorous, but specializations in details point to the possibility to use some food resources in a special effective way.